A hála szerepe lelki, mentális és fizikai egészségünkben - FERENCZI, Andrea (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2020)
The Role of Gratitude in Spiritual, Mental and Physical Health. Psalm 50 demonstrates complicated requirements of relationships towards both God and our neighbours in terms of gratitude, as well as in the realm of hope for divine liberation. Having evolved layers of meaning, in the psalm, the expression “liberation” – the linguistic root “jesa” – seems to have wide collocations. Getting released from an enemy is the immediate equivalent, but the spectrum of meaning covers, among others, escape from exigency, psychological burden, or bodily disease. We started to examine interrelations between gratitude and liberation with psychological means some years ago. Through exploring terrains of gratitude as a construct, we hope to get closer to the understanding of human nature and behaviour. Our results may serve therapeutic intervention by bringing closer those who are engaged in counsellor and psychology professionals. My present study wishes to describe the notion of gratitude from the perspectives of religious and cultural studies and more broadly, from the aspects of psychology. The review of some research results is meant to underline interrelations between gratitude and mental health. Finally, some of our own researches support the idea that gratitude is a capacity you can acquire and improve throughout your life. Experiencing and expressing gratitude may provide room for something new and may afford space for recovery to happen, for willingness to occur, so that liberation could come into being.